2017
DOI: 10.1590/1980-57642016dn11-010014
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary approach aiding the diagnosis of primary progressive aphasia: A case report

Abstract: Frontotemporal dementia (FTD) is one of the most common causes of early-onset dementia with primary progressive aphasia (PPA) being the second-most-frequent form of this degenerative disease. Despite the similarity with progressive dementia (especially in early stages of Alzheimer´s disease), three types of PPA can be differentiated: semantic, agrammatic and logopenic (subtype discussed in this study). To date, no medications have been shown to improve or stabilize cognitive deficits in patients with PPA. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In the field of pharmacological interventions, to date, no medications have been shown to improve or stabilize cognitive deficits in patients with PPA [ 29 ]. Indeed, clinical trials on patients with FTD and controlled trials on PPA patients with bromocriptine [ 30 ] and memantine [ 31 ] have not demonstrated any efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of pharmacological interventions, to date, no medications have been shown to improve or stabilize cognitive deficits in patients with PPA [ 29 ]. Indeed, clinical trials on patients with FTD and controlled trials on PPA patients with bromocriptine [ 30 ] and memantine [ 31 ] have not demonstrated any efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In the eld of pharmacological interventions, to date, no medications have been shown to improve or stabilize cognitive de cits in patients with PPA [27]. Indeed, clinical trials on patients with FTD and controlled trials on PPA patients with bromocriptine[28] and memantine [29] have not demonstrated any e ciency.…”
Section: Discussionmentioning
confidence: 99%